Impacts caused by the closure of schools in the countryside in the municipality of Arraias in the conception of the protagonists - Luiz Felipe de Castro Varanda; Helena Quirino Porto Aires (Revista Brasileira de Educação do Campo)
This study is an excerpt from the Undergraduate Thesis in Pedagogy at the Federal University of Tocantins (UFT) and aims to analyze the school closure policy and the process of school nucleation in the municipality of Arraias (TO), as well as the impacts resulting from these measures. The research adopts a qualitative approach, based on bibliographic and field investigation. The data collection instruments include document analysis and semi-structured interviews conducted with students and parents/guardians residing in rural areas who study in the city, as well as teachers who receive these students. The research findings indicate that, in less than two decades, more than 48 schools have been closed, highlighting the precarious state of rural education and the incomplete implementation of municipal public policies. Among the main impacts of this scenario are the uprooting of students from their communities, their insertion into a context that differs from their cultural habits and customs, and the need for long daily commutes, often exceeding eight hours in school transportation. Given this reality, it is expected that this study will contribute to fostering a critical reflection on school closure and nucleation, as well as on public policies aimed at rural education.